Measuring critical deficits in shared decision making before elective surgery - Ankuda, Claire K.; Block, Susan D.; Cooper, Zara; Correll, Darin J.; Hepner, David L.; Lasic, Morana; Gawande, Atul A.; Bader, Angela M. (Patient education and counseling, 2014)
Identifying patient factors correlated with specific needs in preoperative decision making is of clinical and ethical importance. We examined patterns and predictors of deficiencies in informed surgical consent and shared decision-making in preoperative patients. Validated measures were used to survey 1034 preoperative patients in the preoperative clinic after signed informed consent. Principal component analysis defined correlated groupings of factors. Multivariable analysis assessed patient factors associated with resultant groupings. 13% of patients exhibited deficits in their informed consent process; 33% exhibited other types of deficits. Informed consent deficits included not knowing the procedure being performed or risks and benefits. Other deficits included not having addressed patient values, preferences and goals. Non-English language and lower educational level were factors correlated with higher risk for deficits. Deficits exist in over a third of patients undergoing preoperative decision-making. Sociodemographic factors such as language and educational level identified particularly vulnerable groups at risk for having an incomplete, and possibly ineffective, decision-making process. Interventions to identify vulnerable groups and address patient centered surgical decision making in the pre-operative setting are needed. Focused interventions to address the needs of at-risk patients have potential to improve the surgical decision-making process and reduce disparities.